N-acetylcysteine Amide AD4/NACA and Thioredoxin Mimetic Peptides Inhibit Platelet Aggregation and Protect against Oxidative Stress - Sonia Eligini; Marco Munno; Daphne Atlas; Cristina Banfi (MDPI AG, 2023)
In the present study, we tested the effect of small-molecular-weight redox molecules on collagen-induced platelet aggregation. We used N-acetylcysteine amide (AD4/NACA), the amide form of N-acetylcysteine (NAC), a thiol antioxidant with improved lipophilicity and bioavailability compared to NAC, and the thioredoxin-mimetic (TXM) peptides, TXM-CB3, TXM-CB13, and TXM-CB30. All compounds significantly inhibited platelet aggregation induced by collagen, with TXM-peptides and AD4 being more effective than NAC. The levels of TxB2 and 12-HETE, the main metabolites derived from the cyclooxygenase and lipoxygenase pathways following platelet activation, were significantly reduced in the presence of AD4, TXM peptides, or NAC, when tested at the highest concentration (0.6 mM). The effects of AD4, TXM-peptides, and NAC were also tested on the clotting time (CT) of whole blood. TXM-CB3 and TXM-CB30 showed the greatest increase in CT. Furthermore, two representative compounds, TXM-CB3 and NAC, showed an increase in the anti-oxidant free sulfhydryl groups of plasma detected via Ellman's method, suggesting a contribution of plasma factors to the antiaggregating effects. Our results suggest that these small-molecular-weight redox peptides might become useful for the prevention and/or treatment of oxidative stress conditions associated with platelet activation.